ANALISIS PERAN GURU DALAM PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) DI KELAS III SD NEGERI 13 LAUNG TAHUN PELAJARAN 2024/2025 - Ariska, Lasarus; Parida, Lusila; Warkintin, Warkintin (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to describe the role of teachers in implementing the Problem Based Learning (PBL) model in Grade III elementary school. The research employed a qualitative descriptive approach, with teachers and Grade III students at SD Negeri 13 Laung, Kecamatan Seberuang, Kabupaten Kapuas Hulu as the subjects. Data were collected through observation, interviews, and documentation, and analyzed using Miles and Huberman’s interactive model. Data validity was ensured through triangulation techniques. The results indicate that (1) the implementation of PBL not only successfully achieved the learning objectives on rights and obligations but also enhanced students’ critical thinking, problem-solving, and collaboration skills; (2) students’ responses to PBL were very positive, showing active engagement, improved problem-solving and social skills, increased independence and learning motivation, and long-term benefits in developing critical thinking abilities. This study demonstrates that PBL effectively supports both cognitive and social-emotional development in elementary school students.